Earthworm Management in Tropical Agroecosystems - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Edited by P Lavelle (University of Paris VI/IRD, France), L Brussaard (Wageningen UR, The Netherlands), and P Hendrix (University of Georgia, USA). CABI. 1999. 320 pp.ISBN 0851992706.£49.95 $95.00 Euro 91.35(See earlier CABI reference for...